No Evidence of Unexpected Transgenic Insertions in T1190 – A Transgenic Apple Used in Rapid Cycle Breeding – Following Whole Genome Sequencing - Patocchi, Andrea; Keilwagen, Jens; Berner, Thomas; Wenzel, Stefanie; Broggini, Giovanni A. L.; Altschmied, Lothar; Hanke, Magda-Viola; Flachowsky, Henryk (Frontiers in Plant Science, 2021)
Rapid cycle breeding uses transgenic early-flowering plants as crossbred parents to facilitate the shortening of breeding programs for perennial crops with long-lasting juvenility. Rapid cycle breeding in apple was established using the transgenic genotype T1190 expressing the BpMADS4 gene of silver birch. In this study, the genomes of T1190 and its non-transgenic wild-type PinS (F1-offspring of 'Pinova' and 'Idared') were sequenced with Illumina short-read sequencing in two separate experiments resulting in a mean sequencing depth of 182x for T1190 and 167x for PinS. Sequencing revealed 8,450 reads, which contain sequences of ≥20 bp identical to the plant transformation vector. These reads were assembled in to 125 contigs, which were examined to see whether they contained transgenic insertions or not using a five-step procedure. The sequence of one contig represents the known T-DNA insertion on chromosome 4 of T1190. Sequences of the remaining contigs were either equally present in T1190 and PinS, their part with sequence identity to the vector was equally present in apple reference genomes, or they seem to result from endophytic contaminations, rather than from additional transgenic insertions. Therefore, we conclude that the transgenic apple plant T1190 contains only one transgenic insertion, located on chromosome 4, and show no further partial insertions of the transformation vector.